Engraved gems and propaganda in the Roman Republic and under Augustus - Gołyźniak, Paweł. (Oxford)
viii, 606 sayfa
Keywords: “This book studies small but highly captivating artworks from antiquity – engraved gemstones. These objects had multiple applications, and the images upon them captured snapshots of people's beliefs, ideologies, and everyday occupations. They provide a unique perspective on the propaganda of Roman political leaders, especially Octavian/Augustus. Engraved Gems and Propaganda in the Roman Republic and under Augustus deals with small, but highly captivating and stimulating artwork – engraved gemstones. Although in antiquity intaglios and cameos had multiple applications (seals, jewellery or amulets), the images engraved upon them are snapshots of people's beliefs, ideologies, and everyday occupations. They cast light on the self-advertising and propaganda actions performed by Roman political leaders, especially Octavian/Augustus, their factions and other people engaged in the politics and social life of the past. Gems can show both general trends (the specific showpieces like State Cameos) as well as the individual and private acts of being involved in politics and social affairs, mainly through a subtle display of political allegiances, since they were objects of strictly personal use. They enable us to analyse and learn about Roman propaganda and various social behaviours from a completely different angle than coins, sculpture or literature. The miniaturism of ancient gems is in inverse proportion to their cultural significance. This book presents an evolutionary model of the use of engraved gems from self-presentation (3rd-2nd century BC) to personal branding and propaganda purposes in the Roman Republic and under Augustus (until 14 AD). The specific characteristics of engraved gems, their strictly private character and the whole array of devices appearing on them are examined in respect to their potential propagandistic value and usefulness in social life. The wide scope of this analysis provides a comprehensive picture covering many aspects of Roman propaganda and a critical survey of the overinterpretations of this term in regard to the glyptic art. The aim is the incorporation of this class of archaeological artefacts into the well-established studies of Roman propaganda, as well as the Roman society in general, brought about by discussion of the interconnections with ancient literary sources as well as other categories of Roman art and craftsmanship, notably coins but also sculpture and relief.” --